Kajian Literatur Sistematis Analisa Penerapan Kurikulum Darurat di Sekolah Dasar dalam Konsep Dunia Pendidikan - Prasetia, Anggi (Universitas Tanjungpura, 2023)
Curriculum and education are 2 interrelated concepts, there is no single educational model without a curriculum. And vice versa that the curriculum becomes a way for an education to achieve its goals. This study aims to determine the development of the world of education through the application of an emergency curriculum during the Covid-19 pandemic. That way in this study, a systematic literature review was carried out to answer how the application of this emergency curriculum can be an option and the extent of its effectiveness and examine more deeply what was analyzed by other researchers in previous studies. The method used in this study is a systematic literature review method by Kitchenham. From the search results, more than 200 research articles were found regarding the analysis of the application of the emergency curriculum, but only a few were referenced based on the selection criteria. The conclusion obtained in the study is that the emergency curriculum applied to each school has not been able to be a pioneer in improving a system of decline. Some of the impacts that occur lead to loss learning to loss generation, because the perception and understanding of educators who have not yet globally embraced the implementation of an emergency curriculum system.